Sedentary and Trained Older Men Have Distinct Circulating Exosomal microRNA Profiles at Baseline and in Response to Acute Exercise - Nair, Venugopalan D.; Ge, Yongchao; Li, Side; Pincas, Hanna; Jain, Nimisha; Seenarine, Nitish; Amper, Mary Anne S.; Goodpaster, Bret H.; Walsh, Martin J.; Coen, Paul M.; Sealfon, Stuart C. (Frontiers in Physiology, 2020)
Exercise has multi-systemic benefits and attenuates the physiological impairments associated with aging. Emerging evidence suggests that circulating exosomes mediate some of the beneficial effects of exercise via the transfer of microRNAs between tissues. However, the impact of regular exercise and acute exercise on circulating exosomal microRNAs (exomiRs) in older populations remains unknown. In the present study, we analyzed circulating exomiR expression in endurance-trained elderly men (n=5) and age-matched sedentary males (n=5) at baseline (Pre), immediately after a forty minute bout of aerobic exercise on a cycle ergometer (Post), and three hours after this acute exercise (3hPost). Following the isolation and enrichment of exosomes from plasma, exosome-enriched preparations were characterized and exomiR levels were determined by sequencing. The effect of regular exercise on circulating exomiRs was assessed by comparing the baseline expression levels in the trained and sedentary groups. The effect of acute exercise was determined by comparing baseline and post-training expression levels in each group. Regular exercise resulted in significantly increased baseline expression of three exomiRs (miR-486-5p, miR-215-5p, miR-941) and decreased expression of one exomiR (miR-151b). Acute exercise altered circulating exomiR expression in both groups. However, exomiRs regulated by acute exercise in the trained group (7 miRNAs at Post and 8 at 3hPost) were distinct from those in the sedentary group (9 at Post and 4 at 3hPost). Pathway analysis prediction and reported target validation experiments revealed that the majority of exercise-regulated exomiRs are targeting genes that are related to IGF-1 signaling, a pathway involved in exercise-induced muscle and cardiac hypertrophy. The immediately post-acute exercise exomiR signature in the trained group correlates with activation of IGF-1 signaling, whereas in the sedentary group it is associated with inhibition of IGF-1 signaling. While further validation is needed, including measurements of IGF-1/IGF-1 signaling in blood or skeletal muscle, our results suggest that training status may counteract age-related anabolic resistance by modulating circulating exomiR profiles both at baseline and in response to acute exercise.